Identifying Operational Challenges and Solutions During the COVID-19 Response Among US Public Health Laboratories. Issue 6 (28th November 2022) - Potter, Christina; Kaushal, Natasha; Wroblewski, Kelly; Becker, Scott; Nuzzo, Jennifer B.
Abstract : Context: The ability to diagnose and screen for infection is an important component of the US COVID-19 response and is facilitated by public health laboratories (PHLs). Anecdotal media reports and limited case studies have described some of the challenges faced by PHLs during the pandemic, particularly initial challenges related to developing and deploying tests to PHLs, but there has not been a systematic evaluation of the experience of PHLs during the pandemic. Objective: To document challenges and lessons learned experienced by local and state PHLs during the COVID-19 pandemic to support generation of best practices for current and future similar emergencies. Design, Setting, and Participants: From February to June 2021, researchers conducted 24 interviews with 68 leaders and staff representing 28 local and state PHLs across 27 states. Thematic analysis of interview content documented operational challenges and any identified solutions or preventive measures used or proposed. Main Outcome Measures: Analysis identified the following themes regarding challenges faced among PHLs: strategic decision making and determining the mandate of the PHL; political interference by jurisdictional leadership; federal mismanagement of the emergency; regulatory challenges; managing partnerships with other laboratories; acquisition of appropriate supplies; insufficient information systems; acquiring and retaining workforce; and difficulty accessing sufficient funding. Results: Within the identified themes, key informants provided further elaboration regarding how PHLs experienced, evaded, or solved these challenges. In addition, PHLs described how challenges evolved throughout the course of the COVID-19 pandemic and made proposals regarding how challenges could be prevented or further addressed in the future by laboratories or other decision makers and stakeholders. Conclusions: While fellow laboratories and political leadership may gain inspiration from creative solutions employed by PHLs, recognition of long-standing gaps related to funding, laboratory workforce, and consideration of laboratory needs in preparedness policies must be addressed for future large-scale outbreaks.